Bibliometric Analysis of Studies on Cultural Heritage Tourism - Kodalak, Oğuzhan; Baltacı, Mahmut (My University, 2023)
From a historical viewpoint culture is a way of life that shows the continuity of societies and is characterized by material and spiritual characteristics transferred from generation to generation. With the globalization movements in the world, it has been seen that the cultural formations formed within the scope of values with material and spiritual characteristics have crossed their own borders and started to attract attention throughout the world. Cultural heritage is defined as all kinds of physically existing works made by people and values belonging to a society inherited from the past and desired to be transferred to the future for different reasons. This study, it is aimed to express the bibliometric features of the studies published on cultural heritage tourism. In this direction, 603 publications in the Scopus database between 2014 and 2023 were analyzed using the bibliometric analysis technique. Because of the findings, the basic data on the concept of cultural heritage tourism was visualized with the help of analysis tables and mapping techniques such as the most cited authors, the most frequently published universities and journals, the most frequently used words, and international collaborations
Keywords: Culture; Bibliometric Analysis; Sustainable Development; Cultural Tourism; Cultural Heritage Tourism